Fused filament fabrication of continuous optic fiber reinforced polylactic acid composites. Issue 4 (10th December 2021) - Yan, Rui; Wang, Yuye; Luo, Pengjun; Li, Yangbo; Lu, Xiaochun
Abstract : Purpose: The limited strength of polylactic acid (PLA) hinders its extensive engineering applications. This paper aims to enhance its strength and realize diverse applications. Design/methodology/approach: Here, the continuous fiber reinforced PLA composites are fabricated by a customized fused filament fabrication three-dimensional printer. Uniaxial tensile and three-point flexural tests have been conducted to analyze the reinforcement effect of the proposed composites. To unveil the adhering mechanism of optic fiber (OF) and PLA, post failure analysis including the micro imaging and morphology have been performed. The underlying mechanism is that the axial tensile strength of the OF and the interfacial adhesion between PLA and OF compete to enhance the mechanical properties of the composite. Findings: It is found that 10%–20% enhancement of strength, ductility and toughness due to the incorporation of the continuous OF. Originality/value: The continuous OFs are put into PLA first time to improve the strength. The fabrication method and process reported here are potentially applied in such engineering applications as aerospace, defense, auto, medicine, etc.